A Decentralized Control Method for a Low-Voltage DC Microgrid - Khorsandi, Amir; Ashourloo, Mojtaba; Mokhtari, Hossein (IEEE transactions on energy conversion, 2014)
DC microgrids (DC-MGs) are becoming popular as an effective means to integrate various renewable energy resources. Conventionally, the droop control is adopted as a decentralized control strategy for proper power sharing without using any communication link. However, the conventional droop control often deteriorates due to the effects of unequal line resistances. In this paper, a control strategy is proposed for a DC-MG to achieve perfect power sharing considering the effects of line resistances. The DC-MG under study consists of a photovoltaic system, two energy storage systems, a grid-connected converter system, and dc loads. The control strategy of the converters is addressed under various operation modes. To obtain prolonged and reliable operation of the DC-MG, the state of charge of the batteries is also considered in the power sharing strategy. Simulation and experimental results are provided to verify the effectiveness and validity of the proposed method.